Meta-analysis of Queensland's coastal Indigenous fisheries: Examining the archaeological evidence for geographic and temporal patterning. (December 2019) - Lambrides, Ariana B.J.; McNiven, Ian J.; Ulm, Sean
Highlights: Archaeological evidence of Queensland's Indigenous fisheries examined. Ubiquity measures tracked commonly occurring fish species across space and time. Multiple species from diverse habitats were targeted as part of mixed fisheries. Some indications that range of targeted species increased throughout the Holocene. Local ecological knowledge and cultural preference guided species selection. Abstract: Marine fisheries have been a critical part of Aboriginal and Torres Strait Islander people's connection to land and sea country in Queensland, Australia for millennia. However, no archaeological studies have examined regional variability in the role of fish within subsistence regimes or the distribution of targeted fish species throughout the Holocene. We utilised a meta -analysis approach to conduct the first comprehensive assessment of Indigenous fisheries along the eastern Queensland coast. Data from 44 archaeological sites were grouped according to marine bioregion to facilitate broad comparison between sites across the study area. These sites were predominantly associated with mid-to-late Holocene occupation, and provided an assemblage of 45, 052 recovered fish bones, of which 6606 were identified most commonly to family-level. Results indicate clear geographic patterning in the ubiquity of fish species captured, and for some marine bioregions an increase through time in the range of species targeted. Archaeological data indicate mixed species fisheries, with a complex range of habitats and diverse fish species harvested by people in relative proximity to the sites. These harvesting decisions were mediated by local ecological knowledge, awareness of fish behaviour, and cultural preference for certain species. These outcomes support existing models for the region, which document a shift in subsistence regimes during the mid-to-late Holocene, particularly an increased reliance on marine resources and expansion in diet breadth. Future research needs to address geographic gaps in data availability and implement globally recognised ichthyoarchaeological quantification and identification protocols to comprehensively examine geographic and temporal variability in Queensland's Holocene Indigenous fisheries, and contribute to regional models of long-term subsistence change.